EFFECT OF PLANT DERIVED NANOPARTICLES ON SPODOPTERA FRUGIPERDA (LEPIDOPTERA: NOCTUIDAE) - SACHIN S. LONDHE (The Journal of Research ANGRAU, 2025)
The fall army worm (Spodoptera frugiperda), a major pest of maize, is responsible for substantial crop losses worldwide. Conventional chemical insecticides are increasingly limited by issues such as pest resistanceand concerns about human health. The present study investigates the potential of green-synthesized silver nanoparticles (AgNPs) derived from six different plant extracts as an eco-friendly alternative for managing the Spodoptera frugiperda. Larvae were collected from infested maize fields in Nashik district, Maharashtra, India, and subsequently reared under laboratory conditions. Fall armyworms were placed in jars and reared in cages with chickpea, rice and maize flour. Rearing conditions: 27 ± 3°C temperature and 60 ± 5% relative humidity. Plant extracts from six plants (datura, neem, ginger, onion, tobacco and mint) were dried, ground, and filtered. 100 grams of powder were dissolved in 500 ml of distilled water, shaken daily for a week, and then filtered. The solution was heated to 78°C to obtain crude extracts. Silver nanoparticles were synthesized by the reduction of silver nitrate using aqueous extracts from six medicinal plants: Datura stramonium, Azadirachta indica (Neem), Zingiber officinale (Ginger), Allium cepa (Onion), Nicotiana tabacum (Tobacco), and Mentha arvensis (Mint). UV-Visible spectroscopy confirmed the formation of polydisperse AgNPs with an average absorbance peak of around 400 nm. Toxicity was assessed through a leaf-dip bioassay method across concentrations ranging from 1 to 60 ppm, with larval mortality recorded at 24 and 48 hours post treatment. AgNPs synthesized from Datura and Neem exhibited the highest insecticidal activity, resulting in 96% and 85% mortality at 20 ppm, respectively. AgNPs derived from Mentha achieved 88% mortality at 60 ppm, whereas Zingiber-based nanoparticles were the least effective, with 73% mortality at the same concentration. The median lethal concentration (LC50) values were lowest for Datura (1.88 ppm) and Neem (2.61 ppm), indicating superior efficacy, while the highest LC50 was observed for Zingiber (14.91 ppm). Although one-way ANOVA revealed no statistically significant differences in mortality among treatments (p > 0.05), the observed variation in LC50 values suggests practical differences in effectiveness. These findings highlight the potential of plant-mediated silver nanoparticles, particularly those synthesized from Datura stramonium and Azadirachta indica, as promising, sustainable alternatives for managing Spodoptera frugiperda.